Clinico-aetiological Profile and Outcome of Hypernatremic Dehydration in Term Neonates Admitted to the NICU at a Tertiary Care Centre in Udaipur, Rajasthan, India - Sanchi Gagneja; Dileep Goyal; Hemlata Mittal; Savita Shekhawat; Devendra Sareen; Sukhanwar Sing Sandhu (JCDR Research and Publications Pvt. Ltd., 2023)
Introduction: Hypernatremic dehydration is commonly found in the first week of neonatal life. Hypernatremia develops when water loss exceeds sodium loss, as in lactational failure with inadequate breastfeeding, or when sodium intake exceeds water intake disproportionately (salt poisoning), such as when neonates receive concentrated formula or top milk. The common presentations include lethargy, irritability, poor feeding, dehydration, reduced urinary frequency, significant weight loss, and fever. Aim: The aim of this study was to investigate the clinico-etiological profile and outcome of hypernatremic dehydration in term neonates admitted to the Neonatal Intensive Care Unit (NICU) at a tertiary care centre. Additionally, the study aimed to examine the factors contributing to hypernatremic dehydration. Materials and Methods: This prospective cohort study was conducted at the NICU, Department of Paediatrics, of Geetanjali Medical College, Udaipur, Rajasthan, India from February 2021 to July 2022. A total of 51 term neonates with a history of inadequate breastfeeding, maternal history of lactational failure, significant weight loss (>10% weight loss within a short period of time), or dehydration fever, along with hypernatremia (serum sodium > 145 mEq/L), were enrolled in the study. Data regarding serum sodium level, serum bilirubin level, Kidney Function Test (KFT), Ultrasonography of Kidney, Ureters and Bladder (USG KUB), and neuroimaging were collected for all study subjects and statistically analysed using the Chi-square test. Results: A total of 51 neonates were admitted to the NICU during the study period, with a mean age of 6.05±2.2 days (range 0-15 days) and a mean birth weight of 2810 grams. The study showed that the mean weight (in %) loss was 13.75±4.1 (range 10.1-21%). The study also revealed that 64.7% of the mothers of neonates experienced lactational failure, with a p-value <0.05. The presenting complaints were poor feeding (92.2%), fever (45.1%), excessive crying (96.1%), and decreased urine output (47%). The mean Standard Deviation (SD) sodium level on admission was 155.3 mEq/L. Two neonates developed neurological complications (intracranial haemorrhage and cerebral oedema), and 62.7% of neonates developed Acute Kidney Injury (AKI). Conclusion: Hypernatremic dehydration poses a significant threat in early neonatal life and is often underdiagnosed. Common causes include a lack of awareness about exclusive breastfeeding, lactational failure, and improper breastfeeding techniques, as well as feeding problems due to inverted/flat nipples or cracked nipples/breast engorgement. These findings were observed in the present study.